Expert elicitation as a method for exploring illegal harvest and trade of wild meat over large spatial scales. Issue 2 (29th February 2016) - Swan, Natalie; Barlow, Jos; Parry, Luke
Abstract: New evidence of commercialization and consumption of wild meat in Amazonian cities has exposed an alarming yet poorly understood threat to Neotropical biodiversity. In response to the limitations of field sampling for large-scale surveys, we sought to develop a method of rapidly assessing wildlife harvest and trade in multiple areas using expert knowledge. Using caiman as a model taxon, we surveyed experts across the Brazilian Amazon. Expert responses to a Likert-style questionnaire suggest that caiman hunting, generally considered a localized rural activity, is in fact common and geographically widespread. Contrary to previous assumptions we found evidence that urban demand is partly driving the harvest, including via interstate trafficking. We highlight the need for further field validation of wild-meat trade and urban consumption patterns in Amazonia. We conclude that expert elicitation is a simple, cost-effective technique that can be a valuable precursor to inform and direct applied conservation research, especially where there are significant knowledge gaps and at large spatial scales.